Linguodidactic School «Language and Speech» of F. de Saussure on the Formation of Language Identity (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is sanctified to the problem of development of sociocultural determinants of forming of language personality on material of school of «language and speech « of F. Dе Saussure. Historical development of sociocultural component of forming of language personality is analyzed in the context of general concept of speech activity the constituents of that are a language.
Keywords: cross-cultural communication; school of «language and speech» of F. dе Saussure sociocultural component of language personality; forming of language personality, European educational space